Ancestral plastics exposure induces transgenerational disease-specific sperm epigenome-wide association biomarkers. Issue 1 (20th March 2021) - Thorson, Jennifer L M; Beck, Daniel; Ben Maamar, Millissia; Nilsson, Eric E; Skinner, Michael K
Abstract: Plastic-derived compounds are one of the most frequent daily worldwide exposures. Previously a mixture of plastic-derived toxicants composed of bisphenol A, bis(2-ethylhexyl) phthalate, and dibutyl phthalate at low-dose exposures of a gestating female rats was found to promote the epigenetic transgenerational inheritance of disease to the offspring (F1 generation), grand-offspring (F2 generation), and great-grand-offspring (F3 generation). Epigenetic analysis of the male sperm was found to result in differential DNA methylation regions (DMRs) in the transgenerational F3 generation male sperm. The current study is distinct and was designed to use an epigenome-wide association study to identify potential sperm DNA methylation biomarkers for specific transgenerational diseases. Observations indicate disease-specific DMRs called epimutations in the transgenerational F3 generation great-grand-offspring of rats ancestrally exposed to plastics. The epigenetic DMR biomarkers were identified for testis disease, kidney disease, and multiple (≥2) diseases. These disease sperm epimutation biomarkers were found to be predominantly disease-specific. The genomic locations and features of these DMRs were identified. Interestingly, the disease-specific DMR-associated genes were previously shown to be linked with each of the specific diseases. Therefore, the germline has ancestrally derived epimutations that potentially transmit transgenerational disease susceptibilities. Epigenetic biomarkers for specific diseases could be used as diagnostics to facilitate clinical management of disease and preventative medicine.